Exploring the reach and impact of Gold and Green OA articles in hybrid journals - Monaghan, Jess (Septentrio Conference Series, 2021)
See RECORDING. Does the type of open access that authors choose for their journal articles make a difference to the reach and impact of their research? There are an increasing number of open access policies and mandates, such as Plan S’ policy which was introduced in 2021 for researchers who have been funded by certain members of cOAlition S, and UK Research and Innovation’s policy for UKRI-funded articles from April 2022 and books from 2024. However, some policies intend to exclude authors from selecting OA in hybrid journals by restricting funding only to those journals covered by Transformative Agreements. In addition, some policies seek to increase the availability of Green OA. These policies would seem to conflict with the potential benefits to authors of publishing Gold OA in hybrid journals. In 2021, Springer Nature commissioned an analysis of 60,567 articles published in hybrid journals to explore the impact and reach of different types of articles (non-OA, Gold OA and Green OA). Our findings show not only that Gold OA articles attract more citations, more downloads, and higher Altmetric Attention Scores on average, compared with non-OA articles, but for the first time we will share evidence of a stronger advantage for Gold OA compared to Green OA. We will discuss the potential implications of these findings for authors, and for institutional and funder policy decisions.